The prospect of using unmanned aerial vehicles to maintain an appropriate level of ecological safety - Rafał Parczewski (Defence Science Review, 2021)
Objectives Possibilities of using drones in the ecological safety system. Methods The main purpose of the research conducted in the form of a questionnaire was to get the respondents' opinions on the usefulness of unmanned aerial vehicles (drones) to support the performance of official tasks . (The method of a diagnostic survey with the use of a questionnaire). Results The collected research material showed that the UAVs are useful to carrying out tasks related to environmental protection. The main recommendations for usefulness of drones in the surveyed group of respondents from individual forest districts were as follows: 1) performing tasks related to fire protection; 2) making cartographic materials, inventory of damages caused by abiotic and biotic factors; 3) used to fight forest pests 4) missing persons searching; 5) detection of illegal dumps; 6) animals inventory; 7) water courses beaver dams monitoring; 8) forest health condition assessment and monitoring; 9) the possibility of quick localization of fires in hard-to-reach places; 10) UAV equipped with thermal camera would help in monitoring (animals tracking); 11) tourist traffic monitoring. Conclusions The collected research material shows that UAVs should be used by services and state authorities that perform tasks related to environmental protection. The results of the surveyed group of UAV operators show that drones would be useful in "tracking" illegal garbage dumps. Public services and bodies should use UAVs to monitor illegal garbage dumps. According to the surveyed group, there should be higher fines for throwing waste (garbage) in prohibited areas.